2004
DOI: 10.1023/b:jmsm.0000010102.26218.d1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–carbon composite bearing materials in hip arthroplasty: analysis of wear and biological response to wear debris

Abstract: Ultra-high molecular weight polyethylene wear particles have been implicated as the major cause of osteolysis, implant loosening and late aseptic failure in total hip arthroplasties in vivo. This study initially screened 22 carbon-carbon composite materials as alternatives for UHMWPE in joint bearings. New bearing materials should satisfy certain criteria--they should have good wear properties that at least match UHMWPE, and produce wear particles with low levels of cytotoxic and osteolytic activity. Initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…To address these negative effects, polymer-based composite materials have been introduced for biomedical purposes because of their high strength-to-weight ratio, non-corrosiveness, tailorability, and radiolucency [5][6][7][8][9][10]. For these reasons, many kinds of polymer-based composite materials reinforced with carbon [6,[11][12][13][14][15][16][17][18][19], aramid [20], glass [7,21], and natural fibers [22] have been explored for bone fracture plating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these negative effects, polymer-based composite materials have been introduced for biomedical purposes because of their high strength-to-weight ratio, non-corrosiveness, tailorability, and radiolucency [5][6][7][8][9][10]. For these reasons, many kinds of polymer-based composite materials reinforced with carbon [6,[11][12][13][14][15][16][17][18][19], aramid [20], glass [7,21], and natural fibers [22] have been explored for bone fracture plating.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of using the present composite structure over a clinically used metal plate for repairing femur fracture are its ease of fabrication, its lower cost since the majority of its composition is flax fiber which is abundant in nature, and its unique biomechanical properties. In terms of its static and dynamic mechanical properties, the current CF/Flax/Epoxy has a comparable elastic modulus (axial: 42 GPa, bending: 57 GPa) vs. human cortical bone (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) with superior strength (axial, 400 MPa; bending, 511 MPa; fatigue, 200-220 MPa) vs. human cortical bone [11,26]. In addition, this composite retains its mechanical properties (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…At present, C/C components with large sizes and complicate shapes are extensively used in the fields of aerospace, aviation and industry. However, it is difficult and expensive to prepare large size and complex structure C/C components directly because of their brittle characteristic, high cost of processing as well as long preparation cycle [6][7][8]. One alternative way is to join several small, simple C/C parts into the large, complicated components.…”
Section: Introductionmentioning
confidence: 99%
“…In the current in vitro and in vivo studies we found that the SSLS-PLA scaffolds showed no deleterious effects on human fetal femur-derived cell activity, and the field of bone tissue engineering has successfully used carbon composites in a number of procedures. Lower wear rates and reduced osteolytic and cytotoxicity effects were demonstrated in carbon-carbon composite bearing materials for artificial hip joints [32] and carbon fiber cages have been used in spinal fusions [33] with no adverse complications. Indeed, studies now indicate the osteogenic effect of carbon coatings on orthopedic implants [34].…”
Section: Discussionmentioning
confidence: 99%